Drug Delivery: Sustained Zero‐Order Release of Intact Ultra‐Stable Drug‐Loaded Liposomes from an Implantable Nanochannel Delivery System (Adv. Healthcare Mater. 2/2014). Issue 2 (February 2014) - Celia, Christian; Ferrati, Silvia; Bansal, Shyam; van de Ven, Anne L.; Ruozi, Barbara; Zabre, Erika; Hosali, Sharath; Paolino, Donatella; Sarpietro, Maria Grazia; Fine, Daniel; Fresta, Massimo; Ferrari, Mauro; et al.
<x xml:space="preserve">Abstract</x> Metronomic chemotherapy supports the idea that long‐term administration of chemotherapeutics could be effective against numerous cancers. On page 230, Alessandro Grattoni and colleagues present constant and sustained release of ultrastable drug‐loaded liposomes from an implantable nanochannel delivery system over 18 days. Further, liposome intravasation from subcutaneous delivery is investigated and their biological activity post‐nanochannel release on BT474 breast cancer cells is verified. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>